Utilizing Blockchain Technology to Increase Transparency in Zakat Management - Mokodenseho, Sabil; Syafri, Muhammad; Hasrullah, Hasrullah; Judijanto, Loso (West Science Islamic Studies, 2023)
This research investigates the impact of blockchain technology on the transparency of Zakat management in Indonesia through a quantitative analysis. The study encompasses a diverse sample of 350 participants from various Zakat institutions, analyzing demographic and organizational characteristics. Findings reveal a positive trend in blockchain adoption, with larger organizations and those in urban areas more likely to integrate the technology. Participants generally perceive Zakat management processes as clear and accountable, although improvements in accessibility are identified. Regression analysis demonstrates a statistically significant positive relationship between blockchain adoption and transparency. Challenges include technical barriers and high implementation costs, while opportunities include increased donor trust and operational efficiency gains. Policy implications suggest regulatory frameworks to support institutions, and organizational strategies recommend phased implementation and capacity-building initiatives. The study contributes insights for policymakers, Zakat institutions, and researchers navigating the intersection of traditional charitable practices and innovative technologies.